Public Administration Policy Innovation Towards the Realization of Good Public Policy Governance - Ohoiwutun, Stanislaus Kostka; Zacharias, Tehubijuluw (Asian Journal of Social and Humanities, 2024)
The use of public policy to balance the interests of the public and government has not always worked well. The government's tendency to change or cancel some policies points to overlapping policies, a lack of innovation among public officers, and a low motivation to innovate. Consequently, a novel strategy that might offer significant support in resolving societal issues is needed. Describe and analyze policy innovation in public administration approach and policy innovation toward effective public policy governance was the aim of the research. The first qualitative approach was the methodology used. An academic literature review on public policy science was the method used to gather ideas pertinent to the study of public policy innovation. The collection of data was conducted by means of an examination of many sources and literature, including government records, printed and electronic media, journals, and publications pertaining to public administration and policy innovation. Policy innovation application is modeled by the use of NPS to apply innovative concepts. A method that allows the public the room to cooperate and be focused on performance development views the public in a holistic, compassionate, and humanist manner. 1) Support type; 2) Innovation management; and 3) Qualities in value application will lead to the realization of good public policy governance.